Cervicofacial Venous Malformations Are Associated with Intracranial Developmental Venous Anomalies and Dural Venous Sinus Abnormalities - Brinjikji, W. (AJNR Am J Neuroradiol, 2020)
BACKGROUND AND PURPOSE: Prior studies have suggested an association between the presence of cervicofacial venous malformations and intracranial developmental venous anomalies. We reviewed our institutional cohort of patients with cervicofacial venous malformations and examined the spectrum of intracranial venous anomalies, including developmental venous anomalies, cavernous malformations, and dural venous sinus abnormalities. MATERIALS AND METHODS: Consecutive patients who presented to our institution with cervicofacial venous malformations and underwent postcontrast MR imaging were studied. Three neuroradiologists reviewed brain MRIs for the presence of developmental venous anomalies, dural venous sinus ectasia, and cavernous malformations. The prevalence of developmental venous anomalies in this patient population was compared with an age- and sex-matched control group without venous malformations at a ratio of 1:2. Categoric variables were compared with χ(2) tests. RESULTS: Sixty-three patients with venous malformations met the inclusion criteria with a mean age of 38.3 ± 24.0 years. The overall presence of developmental venous anomalies in patients with venous malformations was 36.5% (23/63) compared with 7.9% (10/126) in controls (P < .001). The prevalence of dural venous sinus ectasia was 9.5% (6/63) compared with 0% for controls (P = .002). One patient with a venous malformation had a cavernous malformation compared with 1 patient in the control group (P = .62). In 73.9% of patients (17/23), developmental venous anomalies were along the same metamere; and in 82.6% of patients, developmental venous anomalies were ipsilateral to the venous malformations. CONCLUSIONS: Our case-control study demonstrated a significant association between cervicofacial venous malformations and cerebral developmental venous anomalies as well as between cervicofacial venous malformations and dural venous sinus abnormalities. Our findings suggest that venous malformations may be the result of a segmental in utero insult to cells involved in cerebrofacial venous development.